Systematic Preventable Trauma Death Rate Survey to Establish the Region-based Inclusive Trauma System in a Representative Province of Korea - Kwon, Junsik; Lee, Jin-Hee; Hwang, Kyungjin; Heo, Yunjung; Cho, Hang Joo; Lee, John Cook-Jong; Jung, Kyoungwon (Journal of Korean medical science, 2020)
Trauma mortality review is the first step in assessing the quality of the trauma treatment system and provides an important basis for establishing a regional inclusive trauma system. This study aimed to obtain a reliable measure of the preventable trauma death rate in a single province in Korea. From January to December 2017, a total of 500 sample cases of trauma-related deaths from 64 hospitals in Gyeonggi Province were included. All cases were evaluated for preventability and opportunities for improvement using a multidisciplinary panel review approach. Overall, 337 cases were included in the calculation for the preventable trauma death rate. The preventable trauma death rate was estimated at 17.0%. The odds ratio was 3.97 folds higher for those who arrived within "1-3 hours" than those who arrived within "1 hour." When the final treatment institution was not a regional trauma center, the odds ratio was 2.39 folds higher than that of a regional trauma center. The most significant stage of preventable trauma death was the hospital stage, during which 86.7% of the cases occurred, of which only 10.3% occurred in the regional trauma center, whereas preventable trauma death was more of a problem at emergency medical institutions. The preventable trauma death rate was slightly lower in this study than in previous studies, although several problems were noted during inter-hospital transfer; in the hospital stage, more problems were noted at emergency medical care facilities than at regional trauma centers. Further, several opportunities for improvements were discovered regarding bleeding control.